PENGARUH KOMPETENSI, DISIPLIN DAN LINGKUNGAN KERJA TERHADAP MUTU PELAYANAN PADA BANK PEMBANGUNAN DAERAH KABUPATEN TOJO UNA-UNA - Treesya, Treesya (Katalogis, 2017)
The study focuses on three independent variables that are competency, discipline, and work environment, and one dependent variable, service quality. Competency refers to 5 dimensions namely: motive, character, self-concept, knowledge, and skills. Discipline refers to regulations, workload, and proud of institution. Work environment covers dimensions of peers, infrastructure, and comfort the workplace. Variable of service quality refers to direct evidence, reliability, responsiveness, guarantee, and empathy. The aim of the study is to determine and analyze simultaneous and partial influence of competency, discipline, and work environment on service quality at The Regional Development Bank of Tojo Una-Una District. Instrument of the study is questionnaires. The study finds that competency, discipline, and work environment simultaneosly and partially have significant influence on service quality at The Regional Development Bank of Tojo Una-Una District.